Impella 5.5 for Preoperative Optimization in the Setting of Ruptured Papillary Muscle - Rekhtman, David; Iyengar, Amit; Han, Jason; Shad, Rohan; Cevasco, Marisa; Szeto, Wilson; Ibrahim, Michael (The Thoracic and Cardiovascular Surgeon Reports, 2025)
Cardiogenic shock in the setting of a ruptured papillary muscle can be extremely challenging to manage. We report two cases of successful and safe hemodynamic optimization with a modern axial-flow temporary left ventricular assist device, the Impella 5.5, prior to mitral valve replacement for this indication.
Keywords: circulatory-assist devices; myocardial infarction; heart failure; mitral valve surgery; myocardial infarction